2023
DOI: 10.3390/ijms241914730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Prophylactic Effect of Bovine Colostrum on Intestinal Barrier Function in Zonulin Transgenic Mice: A Transcriptomic Study

Birna Asbjornsdottir,
Snaevar Sigurdsson,
Alba Miranda-Ribera
et al.

Abstract: The intestinal barrier comprises a single layer of epithelial cells tightly joined to form a physical barrier. Disruption or compromise of the intestinal barrier can lead to the inadvertent activation of immune cells, potentially causing an increased risk of chronic inflammation in various tissues. Recent research has suggested that specific dietary components may influence the function of the intestinal barrier, potentially offering a means to prevent or mitigate inflammatory disorders. However, the precise m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…22 Besides, transcriptomic studies conducted by Asbjornsdottir et al suggested that the bioactive components in bovine colostrum, such as IgG and lactoferrin, might exert anti-inflammatory properties by regulating the NF-κB signaling pathway. 4 Our current research indicated that CTX caused an imbalance between the immunity-related cytokines and destroyed the intestine structure in BALB/c mice, and interestingly, after encapsulating by liposomes, bovine colostrum showed better characteristics for enhancing the IgG levels, rehabilitating the anti-inflammatory cytokines levels, and improving the intestine structure (Fig. 5–7).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…22 Besides, transcriptomic studies conducted by Asbjornsdottir et al suggested that the bioactive components in bovine colostrum, such as IgG and lactoferrin, might exert anti-inflammatory properties by regulating the NF-κB signaling pathway. 4 Our current research indicated that CTX caused an imbalance between the immunity-related cytokines and destroyed the intestine structure in BALB/c mice, and interestingly, after encapsulating by liposomes, bovine colostrum showed better characteristics for enhancing the IgG levels, rehabilitating the anti-inflammatory cytokines levels, and improving the intestine structure (Fig. 5–7).…”
Section: Discussionmentioning
confidence: 63%
“…1 The preliminary compositions that make up BC can be further divided into nutritional components (e.g., trans fatty acids, protein, and vitamins) and bioactive ingredients (e.g., immunoglobulins, growth factors, and hor-mones), among which the nutrient components are mainly responsible for providing energy to the body, while the bioactive ingredients meet the requirements of the body for growth and development and play crucial roles in fighting against diseases. 2,3 The high nutritional value and high bioactive functionality of bovine colostrum have attracted the attention of scientists around the world, and many researchers have revealed that the supplementation of bovine colostrum exhibits various health benefits, such as anti-inflammatory bowel disease (IBD), 2,4 anti-aging, 5 the management of immune-related syndromes, and the improvement of the athletic stamina. 6 Gaspar-Pintiliescu and colleagues co-cultured Candida lipolytica strains with kefir grains to obtain fermented bovine colostrum with high bioactive components, and they found that compared with water-soluble extracts of fermented colostrum, the bovine colostrum rich in bioactive ingredients exhibited better angiotensinconverting enzyme (ACE) inhibition and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Zonulin, considered a tight junction regulator, is associated with conditions such as diabetes and bipolar disorder (Craig Sturgeon and Fasano, 2016 ; Wood Heickman et al., 2020 ). We detected Zonulin expression in different treatment groups, noting that E. coli treatment resulted in Zonulin upregulation, generally considered a sign of intestinal tight junction destruction ( Asbjornsdottir et al., 2023 ; Zhao et al., 2023 ). This aligns with the down-regulation of tight junction-related proteins ZO-1 and Occludin observed previously.…”
Section: Discussionmentioning
confidence: 97%